Fault Location Approach for UPFC based Line Integration Employing Sparse S-Transform - et. al., Mohan P. Thakre, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Incorporation of FACTs controller in transmission lines adversely affects the functioning of distance relaying and hinders the accurateness of a zone of transmission lines that is not permissible. This article represents a unique strategy for locating faults across the UPFC-based transmission system. The fault-finding approach is based on a sparse S-transform (SST). The SST has a computationally high altitude comparison to the initial discreet ST, as it uses selective signal frequency bands and therefore is suitable for various relay application domains. Several faults have been identified, such as including and excluding the UPFC in the computational performance assessment.